Catalina : a novel [large type] - Cornejo Villavicencio, Karla (Random House Large Print, 2024)
"A year in the life of the unforgettable Catalina Ituralde, a wickedly wry and heartbreakingly vulnerable student at an elite college, forced to navigate an opaque past, an uncertain future, tragedies on two continents, and the tantalizing possibilities of love and freedom. When Catalina is admitted to Harvard, it feels like the fulfillment of destiny: a miracle child escapes death in Latin America, moves to Queens to be raised by her undocumented grandparents, and becomes one of the chosen. But nothing is simple for Catalina, least of all her own complicated, contradictory, ruthlessly probing mind. Now a senior, she faces graduation to a world that has no place for the undocumented; her sense of doom intensifies her curiosities and desires. She infiltrates the school's elite subcultures--internships and literary journals, posh parties and secret societies--which she observes with the eye of an anthropologist and an interloper's skepticism: she is both fascinated and repulsed. Craving a great romance, Catalina finds herself drawn to a fellow student, an actual budding anthropologist eager to teach her about the Latin American world she was born into but never knew, even as her life back in Queens begins to unravel. And every day, the clock ticks closer to the abyss of life after graduation. Can she save her family? Can she save herself? What does it mean to be saved? Brash and daring, part campus novel, part hagiography, part pop song, Catalina is unlike any coming-of-age novel you've ever read--and Catalina, bright and tragic, circled by a nimbus of chaotic energy, driven by a wild heart, is a character you will never forget"--